Redesign Struktur Atas Beton Bertulang Dan Atap Baja Pada Pembangunan Gedung Serbaguna dan Olahraga Universitas Subang - Antafani, Achmad Ismail; Yulianto, Yusup; Rosyadi, Rosyd; Permana, Endang Setiadi (MESA (Teknik Mesin, Teknik Elektro, Teknik Sipil, Teknik Arsitektur), 2024)
Subang University (Unsub) is the first university in Subang Regency. On the Subang University campus itself, which consists of several buildings, there is no presentative room that can be used for various activities (multipurpose room). Therefore, it is necessary to re-design the space in a presentative manner in accordance with the construction rules in accordance with the applicable SNI. The re-designminimizes damage to building structures that do not meet the applicable SNI standards, in accordancewith the provisions of SNI 1726:20212 (Procedures for Earthquake Resistance Planning for BuildingStructures) as a Geotechnical Based on Building Structures, SNI 1727: 2013 (Minimum Free StandardsUsed for Building Design), and SNI 2847:2013 (Requirements for Structural Berton Used for Buildings),and the SNI regulations are divided into 4 load categories, such as: Dead Load, Live Load, Wind Loadand Earthquake Load, and used SAP 2000 to process the redesign analysis. The results of the re-designshowed that the design of the dimension column had the highest ratio (0.971), with 2 rafter designs (WF600x200x11x17) (WF 500x200x10x16), with a lot of upper reinforcement (8D22) and lowerreinforcement (5D22).